Formulasi Dan Evaluasi Sediaan Lulur Ekstrak Kayu Manis (Cinnamomum burmani) Dengan Variasi Konsentrasi Trietanolamin - Rahmawati, Sinta; Budi, Setia; Rohama, Rohama; Audina, Mia (Jurnal Pelayanan Kefarmasian dan Sains, 2025)
Background: Scrubs are extracts of natural ingredients from plants made in the form of scrubs used for beauty. One of the natural ingredients known to have proven efficacy as an antioxidant is Black Cumin (Nigella sativa L.) and cinnamon (Cinnamomum burmani). Black Cumin (Nigella sativa L.) contains unsaturated essential fatty acids (linoleic acid and linolenic acid) that function to rejuvenate skin cells and delay the aging process. Objective: Knowing the evaluation of physical quality and the effect of variations in emulgator concentration on the preparation of cream scrubs from black cumin (Nigella sativa L.) combined with cinnamon extract (Cinnamomum burmani). Methods: This research method uses true experimental. Cinnamon extract (Cinnamomum burmani) and black cumin flour (Nigella sativa L.) were made into cream scrub preparations with varying concentrations of triethanolamine. Results: The results showed that the preparation of black cumin (Nigella sativa L.) cream scrub combined with cinnamon extract (Cinnamomum burmani) with varying concentrations of triethanolamine met the organoleptic parameters, homogeneity, pH test and viscosity test but did not meet the parameters of the spreadability test. The concentration variation in each formulation has a difference in the pH test (0.027), viscosity (0.022) and has no difference in spreadability (0.365). Conclusion: Based of the three formulas of black cumin cream scrub with cinnamon extract with varying concentrations of triethanolamine have not met the physical quality evaluation and thus do not show a good variation of emulgator concentration.